2016
DOI: 10.1002/pros.23207
|View full text |Cite
|
Sign up to set email alerts
|

Increased Urinary Adenosine Triphosphate in Patients With Bladder Outlet Obstruction Due to Benign Prostate Hyperplasia

Abstract: Patients with BOO release higher amounts of ATP into the urine than the control group. The high area under the ROC curve suggests that urinary ATP can be a high-sensitive non-invasive biomarker of BOO, which may have a discriminative value of detrusor competence when comparing BPH patients with low urinary flow rates. Prostate 76:1353-1363, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…To our knowledge, this is the first study in humans to demonstrate the utility of these biomarker concentrations. We hypothesize that OAB is characterized by an increase in urothelial ATP release, as observed by increased urinary [ATP] in OAB (Silva‐Ramos et al., 2013), interstitial cystitis (Sun, Keay, De Deyne, & Chai, 2001) and benign prostatic hypertrophy (Silva‐Ramos, Silva, Oliveira, & Correia‐de‐Sá, 2016), with a small decrease in urothelial NO release. Measurement of a combination of urinary biomarkers provides a more sensitive index of small changes in bladder function attributable to disease onset.…”
Section: Discussionsupporting
confidence: 64%
“…To our knowledge, this is the first study in humans to demonstrate the utility of these biomarker concentrations. We hypothesize that OAB is characterized by an increase in urothelial ATP release, as observed by increased urinary [ATP] in OAB (Silva‐Ramos et al., 2013), interstitial cystitis (Sun, Keay, De Deyne, & Chai, 2001) and benign prostatic hypertrophy (Silva‐Ramos, Silva, Oliveira, & Correia‐de‐Sá, 2016), with a small decrease in urothelial NO release. Measurement of a combination of urinary biomarkers provides a more sensitive index of small changes in bladder function attributable to disease onset.…”
Section: Discussionsupporting
confidence: 64%
“…In the pig, partial bladder outlet obstruction resulted in reduced contractions in response to electrical field stimulation as well as to purinergic agonists ( Milicic et al, 2006 ), but in the rat partial outlet obstruction model, contractions to ATP were increased after 2 weeks and 3 months ( Murakami et al, 2008 ). Patients with bladder outflow obstruction release higher amounts of ATP into the urine ( Silva-Ramos et al, 2016 ).…”
Section: Diseases Of the Lower Urinary Tractmentioning
confidence: 99%
“…Participants in our study had, on average, relatively lower OAB symptom score severity (Table 1) compared to previous studies, however, the observation of significant correlations with the total ICIQ‐OAB symptom scores suggests that ATP is elevated even with mild OAB; an observation that adds weight to the argument that it could be a useful diagnostic biomarker. However, studies have shown that ATP is elevated in pyuria 15 ; interstitial cystitis 16 ; and BPH, 17 so a lack of specificity may limit its usefulness. Future studies may want to include additional measures (such as more detailed questionnaires of urinary symptoms) to be certain of excluding these groups when recruiting from the general population.…”
Section: Discussionmentioning
confidence: 99%